The association of systemic microvascular changes with lung function and lung density: a cross-sectional study. - Bianca Harris (Public Library of Science (PLoS), 2012)
Smoking causes endothelial dysfunction and systemic microvascular disease with resultant end-organ damage in the kidneys, eyes and heart. Little is known about microvascular changes in smoking-related lung disease. We tested if microvascular changes in the retina, kidneys and heart were associated with obstructive spirometry and low lung density on computed tomography. The Multi-Ethnic Study of Atherosclerosis recruited participants age 45-84 years without clinical cardiovascular disease. Measures of microvascular function included retinal arteriolar and venular caliber, urine albumin-to-creatinine ratio and, in a subset, myocardial blood flow on magnetic resonance imaging. Spirometry was measured following ATS/ERS guidelines. Low attenuation areas (LAA) were measured on lung fields of cardiac computed tomograms. Regression models adjusted for pulmonary and cardiac risk factors, medications and body size. Among 3,397 participants, retinal venular caliber was inversely associated with forced expiratory volume in one second (FEV(1)) (P<0.001) and FEV(1)/forced vital capacity (FVC) ratio (P = 0.04). Albumin-to-creatinine ratio was inversely associated with FEV(1) (P = 0.002) but not FEV(1)/FVC. Myocardial blood flow (n = 126) was associated with lower FEV(1) (P = 0.02), lower FEV(1)/FVC (P = 0.001) and greater percentage LAA (P = 0.04). Associations were of greater magnitude among smokers. Low lung function was associated with microvascular changes in the retina, kidneys and heart, and low lung density was associated with impaired myocardial microvascular perfusion. These cross-sectional results suggest that microvascular damage with end-organ dysfunction in all circulations may pertain to the lung, that lung dysfunction may contribute to systemic microvascular disease, or that there may be a shared predisposition.